Adolescents’ Subjective Well-Being of Indonesian Migrant Worker’s Families: The Role of Social Support and Parental Communication - Feby Sawitri; Alfiasari Alfiasari (Komunitas, 2023)
Subjective well-being is the perception of happiness and satisfaction with life experiences from someone's point of view. This research aims to analyze the effect of adolescent characteristics, family characteristics, social support, and adolescent-parental communication on the subjective well-being of adolescents in migrant worker families. The method used in this research is a non-probability sampling method with a convenience sampling technique in 5 selected schools in the Kesugihan District, Cilacap Regency, Central Java. The respondents of this study involved 99 junior high school students aged 12-16 years. Based on the results, teenagers whose parents leave behind to work overseas predominantly live with their grandparents. Migrant workers are dominated by mothers, with percentages up to 85.9 percent, and most work as household assistants. Migrant workers are dominated by married persons and belong to the small family category. Teacher social support for PMI family teenagers has an average index of 62.55, and peer social support is 63.67. The study also found that mother communication with adolescents is better than father communication with adolescents. The correlation test results stated that teacher social support, peer social support, and parent-adolescent communication had a significant positive relationship with adolescent subjective well-being.